2007
DOI: 10.1093/ps/86.1.87
|View full text |Cite
|
Sign up to set email alerts
|

Growth Performance and Ileal and Total Tract Amino Acid Digestibility in Broiler Chickens Fed Diets Containing Bacterial Protein Produced on Natural Gas

Abstract: A total of 180 broiler chickens were fed 1 of 3 diets from day-old to slaughter at 35 d: a control diet with 35% soybean meal (SOY) or diets in which either 6% basic bacterial protein meal (BBP) or 6% autolysed bacterial protein meal (AUT) partially replaced soybean meal protein. Ileal and total tract apparent amino acid digestibility were examined in 5 chickens per diet using TiO(2) as an inert marker. Chickens fed the diets with bacterial protein had higher weight gain and feed consumption than control chick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2009
2009
2025
2025

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 17 publications
0
27
0
Order By: Relevance
“…Previously, Skrede et al (2003) had reported lower abdominal fat pad content in broiler chickens fed 60 or 90 g/kg BPM at the expense of SBM, compared with chickens fed a control diet containing no BPM. Schøyen et al (2007b) found no effect on abdominal fat pad content in broiler chickens fed up to 60 g/kg BPM at the expense of fish meal, but did show a tendency towards lower levels of abdominal fat when SBM was replaced by BPM. Furthermore, Hellwing et al (2006) reported no effect of feeding up to 60 g/kg BPM at the expense of fish meal on carcase composition in chickens.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Previously, Skrede et al (2003) had reported lower abdominal fat pad content in broiler chickens fed 60 or 90 g/kg BPM at the expense of SBM, compared with chickens fed a control diet containing no BPM. Schøyen et al (2007b) found no effect on abdominal fat pad content in broiler chickens fed up to 60 g/kg BPM at the expense of fish meal, but did show a tendency towards lower levels of abdominal fat when SBM was replaced by BPM. Furthermore, Hellwing et al (2006) reported no effect of feeding up to 60 g/kg BPM at the expense of fish meal on carcase composition in chickens.…”
Section: Discussionmentioning
confidence: 68%
“…We found similar growth rate, reduced feed intake and improved FCE of birds fed increasing concentrations of BPM compared with the SBM control. Previous studies have shown that feeding BPM to broiler chickens results in similar or improved growth up to 60 g/ kg (Skrede et al, 2003;Schøyen et al, 2007b), but reduced growth rates at higher inclusion concentrations of 80 and 100 g/kg, when replacing SBM (Skrede et al, 2003). Significantly better FCE has also been obtained with increasing concentrations of up to 100 g/kg BPM (Skrede et al, 2003;Schøyen et al, 2007a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The final product is a reddish/ brownish meal, containing about, %: dry matter (DM) 96, crude protein (CP) 70, lipids 10 and ash 7. The BPM has been reported to have a nutritionally favourable amino acid composition (Skrede et al, 1998), and to be a suitable protein source for pigs (Øverland et al, 2001), broiler chickens (Skrede et al, 2003;Schøyen et al, 2007), mink (Ahlstrøm et al, 2006) and salmonid fish species (Aas et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…As the dietary level of single-cell protein increases in broiler diet the gain, feed conversion and intake decreased (Jassim et al 1986;Pirmohammadi et al 1999). Schǿyen et al (2007) partially replaced soybean meal with basic bacterial protein (BBP) meal or autolyzed bacterial protein (AUT) meal. They concluded that 6% of either basic or autolyzed bacterial protein can replace soybean meal in diets for broiler chickens without impairing growth performance, and the basic bacterial protein seemed to be a slightly better substitute than the autolyzed protein.…”
Section: Scp In the Diet Of Broilersmentioning
confidence: 99%